Impact of Long-term Polyvinylpyrrolidone Exposure on Gene Expression, Chromatin Structure, and Malondialdehyde Levels in Human Sperm - Mojdeh Sabour; Mahmood Dehghani Ashkezari; Azam Agharahimi; Seyed Morteza Seifati; Seyed Mehdi Kalantar (Journal of Genetic Resources)
In an intracytoplasmic sperm injection (ICSI) procedure, sperm must be immobilized due to its manipulation; therefore, Polyvinylpyrrolidone (PVP) has been used for this purpose. Based on many studies, fertilization rates may be reduced by incubation of sperm in PVP as it changes sperm mitochondria, nucleus, and membrane structures. Since PVP is used widely in infertility centers, it is noteworthy to investigate the side effects of this agent. This study was designed to evaluate the effects of this component on chromatin quality with acridine orange (AO) staining, Malondialdehyde (MDA) levels, and BAX, BCL2, HSP70 (HSPA2), and SOD2 genes expression in different time intervals (0, 15, 30, and 60 minutes). In this research, 25 normal sperm specimens were applied after preparation with the swim-up method. Results showed that incubation of sperm in PVP for 15, 30, and 60 min significantly increased MDA levels and AO percentage rate compared to unexposed spermatozoa to PVP. Furthermore, the expression of BAX, BCL2, HSP70, and SOD2 genes were altered after incubation in a PVP medium at different time intervals. Incubation of sperm in PVP significantly increased the adverse effects after 15 min. Therefore, sperm should not be exposed to PVP for more than 15 minutes during the ICSI procedure. Altogether, results showed that incubation of sperm in a PVP medium during an ICSI procedure for more than 15 min may result in significant changes in the biological features of sperm. Therefore, expediting the ICSI procedure could mitigate the potential adverse effects of PVP on sperm parameters.